Blending functionalised ligands to form multivariate metal–organic framework nanosheets (MTV-MONs) with tuneable surface chemistry. Issue 14 (31st March 2020) - Ashworth, David J.; Foster, Jonathan A.
Abstract : We report a new approach to tuning the properties of metal–organic nanosheets (MONs) by blending functionalised ligands to produce multivariate MONs (MTV-MONs). Abstract : We report a new approach to tuning the properties of metal–organic framework nanosheets (MONs) by blending functionalised ligands to produce multivariate MONs (MTV-MONs). This approach enabled not only fine tuning of the MONs properties, but also resulted in MTV-MONs that show enhanced performance compared to their single-ligand counterparts. Layered copper paddle-wheel based MOFs were synthesised incorporating two or more 2, 5-difunctionalised-benzene-1, 4-dicarboxylate (fu-BDC) ligands. Liquid ultrasonic exfoliation resulted in the formation of nanosheets down to monolayer thickness presenting multiple functional moieties. Blending of ligands with relatively hydrophilic (methoxy-propoxy) and hydrophobic (pentoxy) moieties resulted in MTV-MONs that showed enhanced dispersion in both polar and apolar solvents compared to either single-ligand parent MON as well as intermediary binding properties. Blending of different fu-BDC ligands with different length alkoxy chains (methoxy-pentoxy) allowed incorporation of up to five different ligands within a single MTV-MON, including ligands which do not form this structure individually. This study demonstrates the potential of blending multiple ligands within an MTV-MON to enable fine-tuning of their structure and properties but also create new nanosheets which are more than the sum of their parts.